2005
DOI: 10.1007/s11064-005-7047-5
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine-Induced Sensitization in Mice: Changes in Locomotor Activity and Mesencephalic Gene Expression

Abstract: It is believed that drug-induced behavioral sensitization is an important process in the development of substance dependence. In order to explore mechanisms of sensitization, a mouse model of nicotine-induced locomotor sensitization was established, and effects of the sensitization process on mesencepahlic gene expression were examined. A schedule, which included 3 weeks of intermittent nicotine exposure (0.5 mg/kg, s.c.) and 3 weeks of withdrawal, resulted in locomotor sensitization. Effects of sensitization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 31 publications
7
13
1
Order By: Relevance
“…Our results agree with previous studies that showed that mice are sensitive to the locomotor activating effects of nicotine (Saito et al, 2005;Ulusu et al, 2005). We were concerned that altered activity could influence anxiety measures; accordingly, in addition to using the absolute number of open arms entries as a measure of anxiety, we used the percentage of open arms entries.…”
Section: Methodological Issuessupporting
confidence: 89%
See 1 more Smart Citation
“…Our results agree with previous studies that showed that mice are sensitive to the locomotor activating effects of nicotine (Saito et al, 2005;Ulusu et al, 2005). We were concerned that altered activity could influence anxiety measures; accordingly, in addition to using the absolute number of open arms entries as a measure of anxiety, we used the percentage of open arms entries.…”
Section: Methodological Issuessupporting
confidence: 89%
“…In keeping with previous data (Saito et al, 2005;Ulusu et al, 2005), nicotine exposure alone elicited increased locomotor activity (NIC4VEH, Po0.02; NIC4ETOH, Po0.005; FPLSD). However, ethanol treatment reversed the nicotineinduced increase in locomotor activity as indicated by the significant difference between values for the nicotine and combined exposure groups (NIC4NIC + ETOH, Po0.002; FPLSD) and by the less-than-additive effect of NICOTINE and ETHANOL detected by the NICOTINE Â ETHANOL …”
Section: Anxiety Effectssupporting
confidence: 91%
“…Two independent populations of animals were used to test for two separate doses of therapeutics described in Drugs. Intermittent sensitization protocols were shown to induce strong behavioral sensitization (Robinson and Becker 1986;Vezina and Queen 2000;Kabbaj et al 2002;Saito et al 2005).…”
Section: Behavioral Sensitization To Nicotinementioning
confidence: 99%
“…Intermittent exposure to nicotine, the major addictive agent in tobacco, produces locomotor sensitization in rodents [1,2]. Development of sensitization has been hypothesized to be involved in drug addiction and related to changes in activity of the mesolimbic circuitry [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Development of sensitization has been hypothesized to be involved in drug addiction and related to changes in activity of the mesolimbic circuitry [3][4][5][6]. Global effects of nicotine on gene expression have been studied in smokers [7,8], in rats [9] and mice [2] after intermittent nicotine treatments, in rats after chronic treatment [10][11][12][13], and using in vitro models [14][15][16].…”
Section: Introductionmentioning
confidence: 99%